Celery (Apium graviolens L.) Herba Extract Capsule Formulation as Anti-Ulcer - Shandra Isasi Sutiswa; Asep Abdul Rahman (JURNAL INFO KESEHATAN, 2020)
The use of medicinal plants for medicine has been prevalent since ancient times and various plants are used for public health. One of the plants that is often used in herbal medicine is celery, either directly in the form of vegetables or as an extract from the Apium graveolens L plant. Celery extract has previously been given to white mice, and can significantly protect the gastric mucosa and suppress gastric acid secretion. Traditional medicine derived from plant extracts is generally more desirable in tablet or capsule dosage forms. The objective of this study is to determine the best filler in the celery herb extract capsule formulation. This study used a pure experimental method using celery herb extracts which were formulated in capsule dosage forms. The powder fillers used in this formulation are Avicel 101, Avicel 102, and Amylum maydis. The extract capsules were then evaluated for uniformity of weight and disintegration time. Based on the evaluation results, the capsules formulated with Avicel 102 filler gave the best results with an average weight uniformity of 380.98 ± 4.41 mg and disintegration time of 2.64 ± 0.31 minutes. It is advisable to continue the evaluation of the dissolution test for the capsule preparation which gives the best result.